2018
DOI: 10.3354/dao03281
|View full text |Cite
|
Sign up to set email alerts
|

Edwardsiella piscicida: a significant bacterial pathogen of cultured fish

Abstract: Edwardsiella piscicida, a Gram-negative, facultative aerobic pathogen belonging to the Enterobacteriaceae family, is the etiological agent of edwardsiellosis in fish and a significant problem in global aquaculture. E. piscicida has been reported from a broad geographical range and has been isolated from more than 20 fish host species to date, but this is likely to be an underestimation, because misidentification of E. piscicida as other species within the genus remains to be resolved. Common clinical signs ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
49
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(51 citation statements)
references
References 93 publications
(35 reference statements)
2
49
0
Order By: Relevance
“…To date, antimicrobial susceptibility testing shows that E. piscicida strains isolated from different hosts and geographical regions are susceptible to most commonly used antibiotics for the treatment of edwardsiellosis [4]. However antibiotic abuse represents a problematic method of treating bacterial infections in the aquaculture industry and has led to the evolution of multi-drug resistance strains [5].…”
Section: Introductionmentioning
confidence: 99%
“…To date, antimicrobial susceptibility testing shows that E. piscicida strains isolated from different hosts and geographical regions are susceptible to most commonly used antibiotics for the treatment of edwardsiellosis [4]. However antibiotic abuse represents a problematic method of treating bacterial infections in the aquaculture industry and has led to the evolution of multi-drug resistance strains [5].…”
Section: Introductionmentioning
confidence: 99%
“…Phenotypically indistinguishable from one another, molecular analysis has revealed fish-associated strains of E. tarda often represent one of two recently recognized taxa, E. piscicida (Abayneh, Colquhoun, & Sørum, 2013;Griffin et al, 2013;Yang et al, 2012) and Edwardsiella anguillarum (Shao et al, 2015), which can exhibit varied pathogenicity in different hosts (Reichley, Ware, Greenway, Wise, & Griffin, 2015;Reichley et al, 2018). Edwardsiella piscicida, formerly known as "typical fish pathogenic E. tarda" (Griffin et al, 2014;Sakai, Yuasa, Sano, & Iida, 2009;Yamada & Wakabayashi, 1999), has emerged as a significant pathogen of cultured freshwater and marine teleosts (Reichley et al, 2017;Buján, Toranzo, & Magariños, 2018;Griffin et al, 2018) and has been reported in an elasmobranch (Camus et al, 2016).…”
mentioning
confidence: 99%
“…; Buján et al. ). Recent studies indicated that E. piscicida is 10 times more lethal in hybrids than in Channel Catfish (Reichley et al.…”
Section: Discussionmentioning
confidence: 97%
“…Higher concentrations of potentially toxic nitrogenous wastes and chronic episodes of infectious diseases (septicemias caused by Edwardsiella ictaluri for Channel Catfish and E. piscicida for hybrids) could be the main reasons for reduced survival. Edwardsiella piscicida continues to garner attention as a significant pathogen in global aquaculture 412 Buján et al 2018). Recent studies indicated that E. piscicida is 10 times more lethal in hybrids than in Channel Catfish (Reichley et al 2017a(Reichley et al , 2017b, and assessment of diagnostic case submissions to the Aquatic Research and Diagnostic Laboratory at the Thad Cochran National Warmwater Aquaculture Center revealed that hybrids accounted for approximately 90% of suspect E. piscicida cases from 2013 to 2017 (Griffin et al 2019).…”
Section: Discussionmentioning
confidence: 99%